2013
DOI: 10.1091/mbc.e13-07-0412
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear basket proteins Mlp1p and Mlp2p are part of a dynamic interactome including Esc1p and the proteasome

Abstract: Mlp1p and Mlp2p form the basket of the yeast nuclear pore complex (NPC) and contribute to NPC positioning, nuclear stability, and nuclear envelope morphology. The Mlps also embed the NPC within an extended interactome, which includes protein complexes involved in mRNP biogenesis, silencing, spindle organization, and protein degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
155
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(167 citation statements)
references
References 106 publications
11
155
0
1
Order By: Relevance
“…38,39 In the opisthokonts and plants, the nuclear basket is composed of large (»200-250 kDa) coiled coil proteins, that associate with and coordinate several nuclear peripheral processes, thereby extending NPC functionality. 36,62,[75][76][77][78] Although the 2 nuclear basket proteins are much smaller (»100kDa) in trypanosomes, our study showed by iEM, that they extend an average of 36nm into the nucleoplasm from the center of the TbNPC. 5 Additionally, they have retained similar functions to those in other eukarya, by creating heterochromatin free zones around nuclear pores that are evident by electron microscopy in all eukaryotic nuclei, as well as recapitulating interactions with the spindle organizer.…”
Section: Tms and Alps: Multiple Ways To Tether A Leviathanmentioning
confidence: 47%
“…38,39 In the opisthokonts and plants, the nuclear basket is composed of large (»200-250 kDa) coiled coil proteins, that associate with and coordinate several nuclear peripheral processes, thereby extending NPC functionality. 36,62,[75][76][77][78] Although the 2 nuclear basket proteins are much smaller (»100kDa) in trypanosomes, our study showed by iEM, that they extend an average of 36nm into the nucleoplasm from the center of the TbNPC. 5 Additionally, they have retained similar functions to those in other eukarya, by creating heterochromatin free zones around nuclear pores that are evident by electron microscopy in all eukaryotic nuclei, as well as recapitulating interactions with the spindle organizer.…”
Section: Tms and Alps: Multiple Ways To Tether A Leviathanmentioning
confidence: 47%
“…Predictions of the transmembrane domains obtained from SGD 105 ( Saccharomyces Genome Database; http://yeastgenome.org) and predictions of membrane binding motifs by the HeliQuest webserver 90,106 informed about their proximity to the pore membrane. Previous immuno-EM measurements 107 informed the end-to-end distance for Mlp1 and Mlp2. Low-resolution EM images of the NPC 44 informed the diameter of the distal basket ring (formed by Mlp1 and Mlp2).…”
Section: Methodsmentioning
confidence: 99%
“…The conformations of Mlp1 and Mlp2 each were restrained by an upper harmonic bound at 350 Å and a lower harmonic bound at 230 Å on the distance between the N-terminal and C-terminal beads, based on immuno-EM measurements 107 . In addition, the radius of the distal basket ring was restrained by an upper harmonic bound at 170 Å and a lower harmonic bound at 130 Å on the radial coordinates of the C-terminal beads of Mlp1 and Mlp2, based on low-resolution EM images of the NPC 44 .…”
Section: Methodsmentioning
confidence: 99%
“…Esc1 is still somewhat obscure. Recent work has shown that the protein associates with the Mlp proteins that form the nuclear basket of nuclear pore complexes, as well as a protein network on the inner nuclear membrane (Niepel et al 2013, and references therein). A second anchor is created by interaction of Sir4 with a nucleoporin, Nup170 (Van de Vosse et al 2013).…”
Section: Sir4 and Heterochromatin Anchoring At The Nuclear Membranementioning
confidence: 99%